2016
DOI: 10.1016/j.seppur.2016.05.047
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical assessing the salts effect on the equilibrium of water + acetone + HMIMPF6 ionic liquid system

Abstract: a b s t r a c tThe influence of naturally occurring monovalent NaCl and divalent Na 2 SO 4 salts with anions at near extremes of Hafmester series on liquid-liquid equilibrium (LLE) of the chemical system of {water + acetone + 1-Hexyl-3-methylimidazolium hexafluorophosphate (HMIMPF 6 ) ionic liquid} was studied. The conditions were 298.2 K, atmospheric pressure of 81.5 kPa and salts mass fractions in initial aqueous solutions of 0.05 and 0.10. Results show that salting-out effect was significant, so that enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The experimental LLE data were determined using an equilibrium jacketed cell (about 5 cm 3 volume) equipped with a magnetic stirrer and based on the titration cloud point method as described in the previous works. , The temperature of the cell was controlled by the circulating water, conducted by the external stream of a thermostat (Julabo, Germany) controlled by a thermocouple with an uncertainty of 0.01 K, and its accuracy was examined by means of an accurate thermometer (Amadigit, ad 3000th, percica, Germany). An electronic Ohaus balance (Adventurer, Pro AV264, Switzerland, uncertainty 0.0001 g) was used to weigh all prepared samples to the desired values.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental LLE data were determined using an equilibrium jacketed cell (about 5 cm 3 volume) equipped with a magnetic stirrer and based on the titration cloud point method as described in the previous works. , The temperature of the cell was controlled by the circulating water, conducted by the external stream of a thermostat (Julabo, Germany) controlled by a thermocouple with an uncertainty of 0.01 K, and its accuracy was examined by means of an accurate thermometer (Amadigit, ad 3000th, percica, Germany). An electronic Ohaus balance (Adventurer, Pro AV264, Switzerland, uncertainty 0.0001 g) was used to weigh all prepared samples to the desired values.…”
Section: Methodsmentioning
confidence: 99%
“…When the metal complexes are extracted, chloride anions from the aqueous phase co-extract to the organic phase to preserve charge neutrality of both phases. CaCl 2 was therefore selected as a salting-out agent to facilitate the extraction and to limit the dissolution of IL in the aqueous phase [44].…”
Section: Extraction With [A336][scn]mentioning
confidence: 99%
“…Chen et al 15 have determined the LLE data for the ternary system water + methanol + methyl acetate in the presence of CaCl 2 with various salt ionic concentrations of 5, 10, 20, and 30 wt % and in the absence of the salt at T = 283.15 K. The experimental data were well correlated with the improved Eisen−Joffe equation. The salt effect on the phase equilibrium of the water + acetone + HMIMPF 6 ionic liquid system has been investigated by Saien et al 16 It was found that adding NaCl salt would lead to a decrease in the water distribution coefficient, while Na 2 SO 4 would give rise to an increase in the water distribution coefficient. The results were interpreted by the degree of hydration of salt ions and the influence of anion exchange with ionic liquids.…”
Section: Introductionmentioning
confidence: 99%